Conexões de transformadores de alta frequência para conversores CC-CC PWM de alta potência - Torres, Carla Gondim (2006)
The present work tackles techniques to power distribution in high frequency transformers and for that it presents configurations with your associated winding in series and/or parallel. This work also presents current sharing study to parallel-parallel connection of three transformers applied to DC-DC FB-ZVS-PWM-PS converters, with purpose of to increase the power processing capacity. To verify current sharing through transformers, two of them were maintained with same design parameters and, in the third, varied in ± 10% relative to the others. The analyses and study are validated through the obtained experimental results of the built prototypes.